2020
DOI: 10.1186/s12958-020-00591-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Letrozole on sperm parameters, chromatin status and ROS level in idiopathic Oligo/Astheno/Teratozoospermia

Abstract: Background: This study investigates the effect of letrozole on hormone profiles, semen parameters, body mass index (BMI), degree of oxidative stress and sperm chromatin integrity in men with idiopathic oligo/astheno/ teratozoospermia (iOAT) and T:E 2 ratio ≤ 10. Materials and methods: This study is a longitudinal, prospective, interventional and open-labelled clinical trial. Semen samples were collected from 20 iOAT men with low serum testosterone (T) to estradiol (E 2) ratio (T:E 2 ratio ≤ 10). The participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 60 publications
4
33
0
4
Order By: Relevance
“…Therefore, it seems that letrozole administration modifies the serum hormonal profile In the present study, significantly higher semen index, semen volume, sperm concentration, total sperm per ejaculate, sperm viability, motility, and progressive motility were observed in letrozole-injected aged bucks. This is consistent with many previous studies [6,[10][11][12] which have demonstrated that aromatase inhibitors improved the sperm parameters in ejaculates of men with infertility problems by increasing the testosterone/estradiol ratio. In similar study, Turner et al [24] asserted that spermatogenesis efficiency increased by treating the adult rats with anastrozole, as an aromatase inhibitor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it seems that letrozole administration modifies the serum hormonal profile In the present study, significantly higher semen index, semen volume, sperm concentration, total sperm per ejaculate, sperm viability, motility, and progressive motility were observed in letrozole-injected aged bucks. This is consistent with many previous studies [6,[10][11][12] which have demonstrated that aromatase inhibitors improved the sperm parameters in ejaculates of men with infertility problems by increasing the testosterone/estradiol ratio. In similar study, Turner et al [24] asserted that spermatogenesis efficiency increased by treating the adult rats with anastrozole, as an aromatase inhibitor.…”
Section: Discussionsupporting
confidence: 93%
“…Kooshesh et al [11] indicated that letrozole administration acts as a fertility agent in idiopathic infertile men, reducing protamine deficiency and DNA fragmentation affected by chromatin packaging and apoptosis pathways by stimulating FSH levels.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…The PICO of 25 studies that did not conform to Table 1 were excluded, and four studies were excluded due to unavailable experimental data. Finally, 10 articles [19][20][21][22][23][24][25][26][27][28] met the inclusion criteria for inclusion analysis (Figure 1), including 3 articles in Chinese [19][20][21] and 7 articles in English [22][23][24][25][26][27][28] .…”
Section: The Search Resultsmentioning
confidence: 99%
“…In data reports, most of them adopt the mode of mean and standard deviation, except that Li et al 21 and Tian et al 20 adopt the form of interquartile rang when reporting semen concentration and total sperm count. Adverse reactions were reported in six studies 20,21,[23][24][25]28 . Two studies 19,25 reported pregnancy rates.…”
Section: Basic Information Included In the Studymentioning
confidence: 99%
“…Letrozole is a reversible type 2 aromatase inhibitor that attaches to cytochrome P-450 and inhibits the conversion of testosterone to estradiol and androstenedione to estrone [10]. Therefore, it can increase levels of testosterone and stimulate spermatogenesis [11]. Few scienti c studies also seem to support the therapeutic potential of letrozole in male reproductive health [12].…”
Section: Introductionmentioning
confidence: 99%